1994
DOI: 10.1164/ajrccm.149.5.8173773
|View full text |Cite
|
Sign up to set email alerts
|

Excess collagen in hypertensive pulmonary arteries decreases vascular distensibility.

Abstract: Increased vascular collagen content is a major feature of pulmonary vascular remodeling. The functional role of excess collagen in decreasing pulmonary vascular compliance has not been established. We determined whether there was a correlation between hydroxyproline content of rat pulmonary artery segments and elastance (EPA) of the pulmonary artery bed during development of hypoxic pulmonary hypertension (10% O2, 10 d) and normoxic recovery. EPA was measured by air-filled pressure-volume curves. After 10 d of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
75
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 22 publications
4
75
0
1
Order By: Relevance
“…6A). In previous studies on mice (20,21), rats (4,42), and calves (23), chronic hypoxia has been found to increase elastic modulus. In some of these studies, modulus in a low-strain range was calculated (20,23), and in these cases chronic hypoxia increased the modulus.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…6A). In previous studies on mice (20,21), rats (4,42), and calves (23), chronic hypoxia has been found to increase elastic modulus. In some of these studies, modulus in a low-strain range was calculated (20,23), and in these cases chronic hypoxia increased the modulus.…”
Section: Discussionmentioning
confidence: 82%
“…In PA segments from rats, the elastance (slope of the pressure-volume relationship) (42) and wall stress (27) have previously been found to return to normal with recovery from hypoxia. As predicted, PA stretch and E 2 did not return to normal levels in Col1a1 R/R mice.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations